Analysis and Verification of Compound SRFPI-LADRC Strategy for an Off-Grid Single-Phase Inverter. (13th October 2022) - Lin, Liaoyuan; Li, Haoda; Zhu, Kai; Shi, Lingling; Li, Ping
Abstract : Summary . The linear active disturbance rejection control (LADRC) is mainly applied for tracking a step signal, and it is inadequate to realize satisfactory performance in the control of a single-phase inverter whose reference signal is sinusoidal. In this paper, an improved voltage control strategy based on compound synchronous reference frame proportional-integral (SRFPI) control and LADRC is proposed. The SRFPI and LADRC remain relatively independent without complicating the control parameter design. Detailed theoretical analyses on the compound strategy and its performance are presented, indicating that it inherits the advantages of the two controllers. Moreover, contrast experiments are carried out to verify the feasibility and superiority of the proposed control strategy. The results show that the system achieves a small steady-state error, voltage tracking error, fast transient response, and low total harmonic distortion (THD) when feeding a highly nonlinear load.